An analysis of relations for determining the thermal conductivity of rigid polymer foams - Alsabry, Abdrahman; Nikitsin, Vadim I.; Kofanov, Vladimir Aleksandrovič; Backiel-Brzozowska, Beata (Zielona Góra: Uniwersytet Zielonogórski)
In the paper the authors present the effectiveness of the generalized thermal conductivity method for polymer foams, including modelling their geometrical structure. Calculations of the effective thermal conductivity coefficient are based on the generally accepted assumption of the additivity of different thermal exchange mechanisms in porous media and this coefficient is presented as a sum the coefficients of conductive, radiative, and convective thermal conductivity.
Keywords: thermal insulation; effective thermal conductivity; rigid polymer foam; mathematical model; structure of used polymer foams; analysis of experimental data